Sex differences in connectivity-based prediction of working memory and its neural organization - Lei Zhuo; Ronglong Xiong; Tingting Zhang; Xiaotong Wei; Junjun Zhang; Zhenlan Jin; Ling Li (Cognitive Neurodynamics, 2026)

Bilayer TPU films integrating pH-responsive bromocresol purple–fluorescein indicators and carvacrol/tea tree oil-loaded HKUST-1@alkaline lignin: Visualization, controlled release, and meat preservation - Liuzi Du; Xiaodong Zhai; Xinyang Han; Ke Zhang; Junjun Zhang; Xiaobo Zou; Zhihua Li; Zhikun Yang; Quancai Sun; Ye Peng; Xiaowei Huang (Food Research International, 2026)

A prediction model for aircraft landing–induced bridge impact coefficients based on bayesian optimization and gradient boosting algorithms - Hui Jiang; Yixuan Li; Junjun Guo; Xianfeng Meng; Guangsong Song; Boqian You (Engineering Structures, 2026)

Multi-source data-driven energy consumption optimization of electric and hybrid inland vessels under multiple operating conditions: A verification study based on Pareto and dynamic programming - Junjun Li; Huaju Qi; Bowei Xu (Ocean Engineering, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Dynamic effects of oxytetracycline pollution on greenhouse gas emissions from wetlands: The synergetic regulatory roles of nutrients, DOM and microbiota - Xuecheng Wang; Yanye Li; Yang Li; Lixia Wang; Mingzhe Gao; Deshou Cun; Qichao Zhou; Junjun Chang (Journal of Environmental Chemical Engineering, 2026)

Enzyme-responsive core-shell nanofibers based on zein/gelatin with controlled release of carvacrol for salmon preservation - Xinyang Han; Junjun Zhang; Liuzi Du; Xiaowei Huang; Xiaodong Zhai; Zhihua Li; Jiyong Shi; Xiaobo Zou (Food Chemistry, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Leucobacter faecis sp. nov., a Novel Actinomycete Isolated from Bat Feces of Rousettus and Hipposideros spp. - Yuyuan Huang; Jing Yang; Qinglian Qin; Zedan Yang; Xiaoting Wei; Ziwei Lin; Wenbo Luo; Wudi Wei; Zongxiang Yuan; Li Ye; Junjun Jiang; Shan Lu; et al. (Current Microbiology, 2026)

Feasibility evaluation for cockroach from Periplaneta americana as a new protein feed ingredient in pigs - Zilin Li; Yu Cao; Meng Liu; Jingru Yuan; Jia Li; Wentao Huo; Mingyi Huang; Shuaishuai Kang; Shiyan Sui; Xiaokang Ma; Yujun Wu; Dandan Han; et al. (Animal Feed Science and Technology, 2026)

Optimizing iterative equivalent-weight quality control with matrix inversion for real-time GNSS satellite clock estimation - Yue Tan; Pan Li; Wenju Fu; Ertao Liang; Junjun Yuan (Advances in Space Research, 2026)

Deep-Water Seafloor Undulations Related to Bottom Currents: A Case Study from the Shenhu Canyon Area, Northern South China Sea - Junjun Zhang; Xishuang Li; Xiaoqing Xu; Lejun Liu; Qingjie Zhou (Journal of Marine Science and Engineering, 2026)
Bottom currents and their associated sedimentary structures are key agents in shaping deep-sea morphodynamics, among which the genesis of seafloor undulations is still debated, restricting engineering risk assessment and resource development safety. Based on high-resolution multibeam bathymetry, sub-bottom profiles, and near-bottom current observations, this study analyzes morphological characteristics, internal reflection structures, and near-bottom current dynamic processes of seafloor undulations in the Shenhu canyon area. The results indicate that undulations occur at canyon heads, canyon interfluve, and east side of canyon. The undulations are generally characterized by vertical aggradation, with some sediment waves exhibiting directional crestline migration accompanied by wave merging, indicating the existence of persistent sediment transport processes. Within the canyon, the flow is concentrated and exhibits significant vertical deflection, reflecting the pronounced flow-guiding effect of the confined topography on near-bottom currents, which consequently controls the lateral migration of crestlines on both sides of the canyon and the shaping of seafloor undulations at canyon heads by internal tides. In contrast, in the relatively open canyon interfluve, flow directions are more dispersed, predominantly characterized by weaker currents. These findings contribute to the understanding of deep-water sedimentary dynamic processes and provide a reference for interpreting the genesis of similar deep-water seafloor undulations.

Heterogeneous Response and Zonal Micromechanical Deterioration of Deep Rock-forming Minerals Under Laser Irradiation - Yuanru Li; Mingzhong Gao; Xuemin Zhou; Yanbo Bai; Junjun Liu; Lei Yang; Haichun Hao; Bengao Yang; Jing Xie; Zheng Gao (Rock Mechanics and Rock Engineering, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Gestational exposure to PP-NPs promotes premature placental ageing through global reprogramming of the trophoblast phosphoproteome - Shuxian Li; Kai Wang; Lingbing Li; Zihan Li; Meijuan Zhou; Junjun Guo; Pihai Gong; Meihua Zhang (Journal of Hazardous Materials, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Astrocytic Prostaglandin Transporter SLCO2A1–Ca2+ Maintains Blood–Brain Barrier Integrity Against Ischemia - Taozhi Wang; Manping Yang; Haiyun Guo; Hongyu Ma; Zhenzhen Li; Junjun Kang; Yaomin Guo; Shengxi Wu; Yazhou Wang; Wugang Hou (Neuroscience Bulletin, 2026)

Molecular mapping of a novel non-canonical gibberellin-sensitive dwarfing gene Rht29 in wheat (Triticum aestivum) - Fuqiao Deng; Juanyu Zhang; Yanyan Tang; Furong Huang; Tao Li; Haili Zhang; Jinhui Wang; Junjun Liang; Guangbing Deng; Hai Long (Theoretical and Applied Genetics, 2026)

Performance evaluation and mechanism analysis of different ice particle distribution shape parameter schemes in BCC-AGCM - Pengcheng Lin; Chunsong Lu; Yiming Liu; Xin He; Junjun Li; Tongwen Wu; Yixiong Lu (Atmospheric Research, 2026)

Improving Asian summer monsoon cloud and precipitation simulations through an ice crystal spectral relative dispersion parameterization - Xin He; Chunsong Lu; Jian Cao; Wentao Zhang; Hengqi Wang; Lei Zhu; Junjun Li; Xiaoqi Xu; Xiangjun Shi; Yuan Wang (Science China Earth Sciences, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Dual-functional smart konjac glucomannan-based packaging incorporating gelatin-cellulose nanocrystal-stabilized emulsions and synergistic anthocyanin-curcumin dyes - Shiqi Li; Xingnan Wang; Junjun Wang; Zhouli Wang (Innovative Food Science & Emerging Technologies, 2026)

Carbohydrates: How structural features influence digestion-fermentation kinetic parameters - Ge Zhang; Li Cao; Zhiqiang Sun; Jingyi Huang; Qi Zhu; Lee J. Johnston; Zeyu Zhang; Junjun Wang; Jinbiao Zhao (Food Chemistry, 2026)

Long-term bioaugmentation of a carrier enhanced duckweed-based wastewater treatment system via the addition of activated sludge and denitrifying phosphate-accumulating bacterium - Yonggui Zhao; Ruidong Ma; Xixi Li; Jinquan Li; Tianning Liang; Wei Li; Junjun Chang; Changqun Duan (Ecological Engineering, 2026)

Reassessing the efficacy and safety of trimethoprim-sulfamethoxazole for Pneumocystis jirovecii pneumonia: a retrospective study - Yangmin Hu; Wei Hu; Danyang Li; Fen Lan; Wei He; Meng Chen; Difei Yao; Junjun Xu; Yujin Lai; Haibin Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Influence of calcium-based localized flocculation near drainage body on dredged sludge consolidation under vacuum preloading - Jun Chen; Xingbing Li; Junjun Ni; Guizhong Xu; Chao Liu (Marine Georesources & Geotechnology, 2026)

Antibiotic pollution impedes nitrogen elimination rates and increases N2O emission from wetlands: A multilevel meta-analysis and the mechanisms - Jibao Jia; Yaxin Chen; Yang Li; Yuting Jiang; Deshou Cun; Yun Zhou; Shengjiong Deng; Junjun Chang (Journal of Environmental Chemical Engineering, 2026)

A critical review of phase change material–aerogel flexible composite films for personal thermal management: performance, mechanism, and applications - Xianfei Liu; Hui Wang; Hui Zhang; Fang Wang; Mengjie Li; Bo Wen; Junjun Li; Caixia Zhu (Energy and Buildings, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Mechanisms of Drillability Enhancement and Damage Evolution in Granite Under Coupled Laser-Drill Interaction - Lei Yang; Mingzhong Gao; Bengao Yang; Jing Xie; Zhiqiang He; Junjun Liu; Fei Li; Xuemin Zhou; Kunchen He (Rock Mechanics and Rock Engineering, 2026)

Causal relationships between alzheimer’s disease genetics and brain connectivity alterations: a multi-modal mendelian randomization study with transcriptomic validation of 191 rs-fMRI and 635 DTI neuroimaging traits - Junjun Ji; Zhifan Li; Abao Xing; Gang Luo; Xiaobing Zhai; Wei Xu; Junrong Li; Tao Tan; Ruihong Jia; Yan Yan; Xianbin Zhang; Long Wang; et al. (Brain Imaging and Behavior, 2026)

Decentralized cooperative collision avoidance strategies for conventional and intelligent ships in mixed scenarios - Bowei Xu; Neng Guo; Junjun Li (Ocean Engineering, 2026)

From single-interface LN2 fracturing to CBM stimulation: Temperature optimization and cracking mechanism - Junjun Feng; Hongqing Qiu; Peng Zhang; Wei Li; Xiaofei Liu; Yankun Ma (Fuel, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

Experimental and numerical study of the extreme behavior of double concave friction pendulum bearings - Mingke Li; Rajesh P. Dhakal; Junjun Guo; Zhongguo Guan; Xingqin Chen (Engineering Structures, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Mixed-Traffic Performance Evaluation of Lane Configurations for Trucks at Automated Container Terminals Under Traffic Conflicts - Kuan Xie; Junjun Li; Bowei Xu (Journal of Marine Science and Engineering, 2026)
With the advancement of autonomous driving technologies, automated container terminals (ACTs) are transitioning toward mixed-traffic operations involving unmanned internal container trucks (ITs) and manned external container trucks (ETs). However, the complex interactions in mixed traffic present frequent conflicts and challenges for system performance evaluation. To address this, this study focuses on mixed-traffic ACTs and establishes a comprehensive performance evaluation model based on multi-agent simulation. First, three lane configurations are defined, including segregated unidirectional, mixed unidirectional, and mixed bidirectional. Then, a path interaction point (PIP) modeling method is proposed under traffic conflicts to characterize lane-level motion behaviors and conflict relationships represented by a conflict matrix, based on which an IT access strategy is developed. Second, a multi-level performance evaluation model for ITs is established, and a 3D multi-agent simulation model is developed to support performance evaluation under different lane configurations. Finally, the three lane configurations are evaluated through simulation at both individual and system levels under a baseline scenario, followed by a sensitivity analysis across varying IT–ET task ratios to assess adaptability. Simulation results indicate that the mixed bidirectional lane configuration achieves superior overall performance and robustness.

Nonlinear responses and temporally varying threshold effects of county-level carbon storage on the Loess Plateau in China (1985–2019) - Junjun Wang; Wenbao Lv; Jinxin Miao; Zihan Li; Zhanjun Xu (Environment, Development and Sustainability, 2026)

Effects of multi-source solid waste-based stabilizing materials on the improvement of high-salinity silt - Yongsheng Yao; Chen Liu; Yuchen Wang; Xiyan Chen; Jue Li; Junjun Ni (Transportation Geotechnics, 2026)

Coupled tectonic-climatic-oceanographic dynamics drove the evolution of foraminiferal diversity in South China during the Middle to Late Mississippian - Chao Liu; Junjun Qi; Pedro Cózar; Ismael Coronado; Fei Li; Weiqing Liu; Meng Li; Ping Wang; Xin Li; Xia Hu; Song Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanical and fracture behavior of red sandstone under confining pressure and laser irradiation using CT scanning and uniaxial compression - Xuemin Zhou; Haichun Hao; Lei Yang; Junjun Liu; Jing Xie; Yuanru Li; Lang Zhou; Jiahua Li; Mingzhong Gao (International Journal of Rock Mechanics and Mining Sciences, 2026)

Physically crosslinked polyphenol-chitosan edible coating for the application of walnut kernels during roasting - Xinhui Wang; Junjun Zhou; Bing Qi; Zhou Chen; Siting Li; Aijin Ma; Yingmin Jia (Food Chemistry, 2026)

Effects of foundation types on structural response to tunnelling in sand: A numerical investigation - Jingmin Xu; Zehui Yu; Yan Li; Junjun Ni (Computers and Geotechnics, 2026)

Increasing CO2 and CH4 emissions from constructed wetlands under composite pollution of microplastics and perfluorooctanoic acid: altering the interactions between dissolved organic matter and the functional microbiome - Yun Zhou; Mingwei Li; Shengkun Yang; Deshou Cun; Shengjiong Deng; Erik Jeppesen; Junjun Chang (Chemical Engineering Journal, 2026)

Enhanced osteogenic differentiation of rBMSCs under low-frequency dynamic stimulation of piezoelectric membranes - Jing Liu; Donglin Li; Xiaoqing Liu; Jiahao Zeng; Yuxuan Lu; Weiqiang Fan; Shuncheng Zhang; Yuxuan Jia; Linxuan Zheng; Xin Chen; Hongzhang Deng; Yongmei Wang; et al. (Chemical Engineering Journal, 2026)

Distinct phylogenetic patterns and assembly processes of abundant and rare taxa in traditional grain vinegar fermentation ecosystem - Mingye Peng; Bo Li; Yunli Zhu; Lu Guo; Lei Deng; Zhicong Shen; Zhiwen Jia; Yang Chen; Junjun Gao; Mengzhou Zhou (International Journal of Food Microbiology, 2026)

Multifunctional green tea-loaded alginate/ polyvinyl alcohol aerogel pads: Fabrication, characterization, sustained release, and Salmon preservation - Ke Zhang; Zhihua Li; Yaning Qin; Junjun Zhang; Naymul Karim; Sulafa B.H. Hashim; Haoyang Xu; Xiaowei Huang; Jiyong Shi; Xiaobo Zou (Innovative Food Science & Emerging Technologies, 2026)

Spatiotemporal-controlled bioinspired asymmetric Janus pad incorporating CQDs@Cu-MOF for autonomous humidity-responsive preservation of lettuce - Jianing Zhang; Junjun Zhang; Xiaowei Huang; Xiaodong Zhai; Tianxing Wang; Yang Zhang; Zhihua Li; Jiyong Shi; Xiaobo Zou (Chemical Engineering Journal, 2026)

Reconstructing historical cloud ice water fraction using machine learning and multi-source satellite data from 1983 to 2009 - Dezhi Xiao; Chunsong Lu; Sinan Gao; Jiashan Zhu; Yang Li; Ru Zhou; Junjun Li; Jing Yang; Naifu Shao (Atmospheric Research, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

Shipping network ripple effect: Interactive propagation and impact of risk-failure - Bowei Xu; Qiuju Xiong; Penghui Zhou; Kai Ge; Junjun Li (Ocean Engineering, 2025)

Environmental impact and carbon footprint analysis of rural domestic wastewater treatment plants based on life cycle assessment method: A case study of Fuzhou City, China - Hanwei Huang; Xiaoying Lin; Junjun Chen; Xueping Liu; Zushan Zhuo; Yuqi Li (Journal of Water Process Engineering, 2025)

Greenhouse gas emissions from field-scale surface-flow constructed wetlands fed with different polluted water types: Environmental and microbial drivers - Deshou Cun; Xiaowan Chen; Junjun Chang; Yang Li; Rong Wu; Rufeng Lin; Shengjiong Deng; Erik Jeppesen; Changqun Duan (Journal of Hydrology, 2025)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Experimental study and seismic performance analysis of novel damage-free self-centering devices with variable stiffness, high-energy dissipation and low prestress - Xin Li; Hui Jiang; Liangjiang Chen; Junjun Guo; Yongzheng Zhou; Wenliang Lu; Cong Zeng (Engineering Structures, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Correction: Expression of Nogo-66 receptor in human astrocytoma is correlated with tumor malignancy - Nanxiang Xiong; Jianying Shen; Shuai Li; Junjun Li; Hongyang Zhao (Molecular Biology Reports, 2025)

Plant performance and leachate water quality enhancement using biochar-modified recycled concrete aggregates - Jiaxin Liao; Yi Huang; Senlin Zhu; Junjun Ni; Haoran Yuan; Denian Li; Haowen Guo; Xudong Zhao (Journal of Cleaner Production, 2025)

The effects of dietary astaxanthin on the intestinal microbiota and metabolites, antioxidant capacity, and resistance to Decapod iridescent virus 1 in Macrobrachium rosenbergii - Cui Liu; Qiusheng Jing; Li Wang; Qincheng Huang; Yukun Jie; Yutong Zheng; Tiantian Ye; Junjun Yan; Zhimin Gu (Fish & Shellfish Immunology, 2025)

A Middle Devonian fluvial-delta plain complex from eastern Yunnan, South China: Insights into co-evolution between environments and organisms in an early non-marine system - Junjun Song; Xiaole Zhang; Sha Li; Wenkun Qie; Yi Wang; Honghe Xu (Earth-Science Reviews, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

The effect of stratus clouds on aerosol distribution in South China based on aircraft measurements - Jianqiu Gao; Zhujie Li; Junxia Li; Gang Wang; Chang Chen; Songwei He; Zhiyuan Shu; Shaoyu Hou; Junjun Lin (Atmospheric Research, 2025)

Genetic analysis and localization of aroma candidate genes for rice - Junjun Guo; Xueyu Yang; Liang Gao; Jin Chen; Liang Zhang; Chunlong Zhang; Bo Zhang; Chuyi Wang; Dandan Li; Juan Li; Shihuang Pu; Jiangli Zhang; et al. (Euphytica, 2025)

Coupling renewable energy with urban greening: quantifying the sustainable development potential of photovoltaic-green roofs - Taoyu Chen; Yantong Li; Yi Zhang; Hexu Ji; Xinyu Wang; Junjun He; Qunyue Liu; He Zhang (Sustainable Cities and Society, 2025)

Characteristics and influencing factors of bacterial, archaeal and fungal community assemblage in riparian restored wetlands: The distinctions between the influent and effluent zones - Shengjiong Deng; Deshou Cun; Yang Li; Lixia Wang; Lingwei Kong; Junjun Chang (Process Safety and Environmental Protection, 2025)

Spatiotemporal diversification enables sustainable cotton-soybean production with enhanced yield and reduced emissions - Qingqing Lv; Ning He; Baojie Chi; Shizhen Xu; Zhenhuai Li; Li Wang; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Jianlong Dai; Junjun Nie; Yongjiang Zhang; et al. (Journal of Cleaner Production, 2025)

The interfacial optimization and p-n heterojunction construction in nanozyme for improved laccase-mimic and antibiofouling activities - Xueying Qi; Junjun Lu; Yueming Li; Xinxin Xu (Journal of Environmental Chemical Engineering, 2025)

Polyvinyl alcohol/corn starch-based indicator films integrated with roselle anthocyanins into five metal-organic frameworks for monitoring chilled pork and shrimp freshness - Xiaowei Huang; Ke Zhang; Junjun Zhang; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Zhihua Li (Innovative Food Science & Emerging Technologies, 2025)

Preparation of nanocellulose/tannic acid-stabilized emulsions combined synergistic co-pigments incorporated polysaccharide-based film for fresh-keeping monitoring and efficient preservation - Shiqi Li; Xueer Wang; Xinyan Li; Xingnan Wang; Rui Cai; Yahong Yuan; Tianli Yue; Junjun Wang; Zhouli Wang (Innovative Food Science & Emerging Technologies, 2025)

Perfluorooctanoic acid and concomitant microplastics pollution impact nitrogen elimination processes and increase N2O emission in wetlands through regulation of the functional microbiome - Yun Zhou; Deshou Cun; Yiting Wang; Yuan Wang; Yanye Li; Erik Jeppesen; Junjun Chang (Water Research, 2025)

Machine learning-based sweet spot prediction for lacuscrine shale oil in the Weixinan Sag, Beibu Gulf Basin, China - Ruoxin Huang; Yifan Li; Zhiqian Gao; Caiwei Fan; Junjun You; Ruisi Li; Chengkun Deng; Guocui Li (Marine and Petroleum Geology, 2025)

Effect of blanching times and drying temperatures on the color, moisture migrations, microstructures, phytochemicals, and flavors of chili pepper (Capsicum annuum L.) - Yongkang Xie; Junjun Geng; Ping Li; Yan Zhao; Junhao Han; Hui Yang; Shina Cao (Food Chemistry, 2025)

Polyphenol-based coacervate droplets as building blocks for protocells and prototissues - Qi Xie; Wei Chen; Zijian Huang; Yuan Gao; Haoyu Zhang; Zhanhao Zhou; Samira Batur; Chuansheng Fu; Jiao Zhang; Conglian Yang; Junjun Liu; Li Kong; et al. (Chemical Engineering Journal, 2025)

Hotspot regions of reactive oxygen species production and their environmental impacts in periodically flooded soil environments: A review - Xing Liu; Yvjie Xie; Paul N. Williams; Baoying Wang; Haiyi Chen; Xiaotong Li; Li Zhang; Leyi Wang; Junjun Liu; Yingxin Wu; Jun Luo (Critical Reviews in Environmental Science and Technology, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Erosion processes of lahar travelling on volcanic sediments: Insights from the physical and numerical modeling - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Feng Wan; Jingyu Yao; Guangjie Li; Lingshuai Zhang (CATENA, 2025)

The combined effects of convective entrainment and orographic drag on precipitation over the Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Xiaoqi Xu; Xianghua Wu; Lei Zhu; Xin He; Shiying Wu; Pengcheng Lin (Science China Earth Sciences, 2025)

Effects of dietary long-chain polyunsaturated fatty acids on osmoregulation and salinity adaptation in red tilapia (Oreochromis mossambicus♀ × O. niloticus♂) under salinity stress - Jiaying Xie; Junjun Sun; Yuanyou Li; Shuqi Wang; Douglas R. Tocher; Cuihong You; Zhenqiang An; Dizhi Xie; Cuiying Chen (Fish Physiology and Biochemistry, 2025)

Zebrafish larvae as a model for investigating dual effects of fluoride on bone development - Xin Wang; Junjun Li; Yumei Fan; Xiaodi Zhang; Yanmei Yang; Yanhui Gao (Toxicology and Applied Pharmacology, 2025)

Melatonin improves aluminum tolerance in soybean through modification of cell wall and vacuolar compartmentalization of aluminum - Huanan Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Junjun Huang; Huahua Wang (Journal of Plant Physiology, 2025)

Challenges of high temperature on ultrasonic propagation in coal reservoirs: Insights from moisture desorption and fissure expansion - Junjun Feng; Shigeng Li; Yankun Ma; Yuanfang Qu; Qisong Huang; Houcheng Ding (Gas Science and Engineering, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

A review of the research progress in the enrichment of rare earth resources by biosorbents - Shiyu Shao; Junjun Wang; Hao Zhou; Xinyi Yu; Jue Kang; Min Huang; Zhu Chen; Hongbo Zhao; Guanzhou Qiu; Li Shen (Minerals Engineering, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

Effects of chitosan on restoring spermatogenesis in mice: Insights from gut microbiota and multi-omics analysis - Guitian He; Boqi Zhang; Tong Chen; Caomeihui Shen; Nan Wang; Junjun Yang; Fuqiang Chang; Yue Sui; Xuanqi Yin; Yueying Wang; Sihui Wang; Yaqiu Li; et al. (Food Research International, 2025)

Preparation of photodynamic-controlled release packaging for pork preservation and its visualization - Junjun Zhang; Jianing Zhang; Roujia Zhang; Xiaowei Huang; Zhihua Li; Xiaodong Zhai; Tingting Shen; Jiyong Shi; Xiaobo Zou (Food Chemistry, 2025)

Lake pollution control and restoration: A critical review of strategies and measures for plateau lakes in Southwestern China - Shengjiong Deng; Lingjuan Tao; Yang Li; Ping Lan; Lixia Wang; Deshou Cun; Junjun Chang (Ecological Engineering, 2025)

Integration of Transcriptomics and Metabolomics Reveals Metabolism Dysregulation in HIV-1-Infected Macrophages - Zongxiang Yuan; Chuye Mo; Yiwen Kang; Junhan Zhang; Fengyi Wang; Wudi Wei; Fang Qin; Shihui Huang; Junjun Jiang; Hao Liang; Li Ye (Current Microbiology, 2025)

Data-Driven Carbon Emission Dynamics Under Ship In-Port Congestion - Weiyu Liu; Bowei Xu; Junjun Li (Journal of Marine Science and Engineering, 2025)
Berthing operation heterogeneity across ship types causes significant uncertainty in assessing port congestion and carbon emissions over comparable timeframes. This study quantifies in-port emission dynamics for four cargo ship types (container, liquid bulk, dry bulk, and general cargo) using an operational phase-specific emission accounting model. We propose a hybrid deep learning model that integrates Two-Dimensional Convolutional Neural Networks (2DCNN) with Squeeze-and-Excitation Attention Mechanisms (SEAM) and Bidirectional Long Short-Term Memory Networks (BiLSTM) layers, optimized via the Triangulation Topology Aggregation Optimizer (TTAO) for hyperparameter tuning. Empirical analysis at Ningbo Zhoushan Port shows that liquid bulk carriers emit 23–41% more than other ship types due to extended auxiliary engine/boiler use during cargo handling. The 2DCNN-SEAM model significantly improves BiLSTM prediction accuracy—reducing Mean Absolute Percentage Error (MAPE) by 18.7% and increasing the R2 value to 0.94—by effectively capturing spatiotemporal congestion features. Results confirm that operational congestion is a critical emission multiplier, especially for ships requiring prolonged auxiliary system use during berthing. These insights inform targeted decarbonization strategies for port authorities, prioritizing operational efficiency and energy transition for high-emission ship categories.

Risk–Failure Interactive Propagation and Recovery of Sea–Rail Intermodal Transportation Network Considering Recovery Propagation - Qiuju Xiong; Bowei Xu; Junjun Li (Journal of Marine Science and Engineering, 2025)
Existing research concentrates on analyzing the propagation and recovery of complex network risk or failure under a single model, which makes it difficult to effectively deal with the chain reaction. Concerning the recovery delay caused by the risk–failure interactions, this paper proposes a model for the propagation and recovery of risk–failure interactions. This model not only considers the network risk–failure interactive propagation mechanism but also introduces the load-balancing strategy and repair mechanism. The study quantifies the impact of the station on network resilience after different attack modes. In addition, the resilience metrics based on the station failure are established to accurately represent the resilience evolution of the network during propagation and recovery. Finally, focusing on the Belt and Road transportation network, we explore the evolution of network resilience under the variation of failure station repair time, station risk state recovery rate, and hub station allocation parameters. The simulation results showed that the model reduced the resilience loss through resilience recovery and accelerated the network back to normal in the face of attacks, shortening the station repair time and increasing the station risk recovery rate significantly improved the overall resilience level of the network, and increasing the proportion of hub station balancing based on the residual capacity effectively improved the minimum resilience of the sea–rail intermodal transportation network.

Dual RNA sequencing reveals the interactions mechanism between Aspergillus fumigatus and Synechocystis sp. PCC6803 under Cd(II) exposure - Junjun Wang; Qinghua Tian; Jun Suo; Jue Kang; Hao Zhou; Xinyi Yu; Guanzhou Qiu; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Regulating the valence and size of the active center of Co/Al2O3 catalyst improved the performance and selectivity of NH3-SCO - Shengyi Wu; Jiaxin Li; Junjun Qiu; Chunxue Wang; Fei Wang; Zhao Li; Ping Ning; Kai Li (Journal of Environmental Sciences, 2025)

Facile fabrication of micro-nano structure on Polydimethylsiloxane film surface for enhancing material recognition accuracy of machine learning-assisted triboelectric nanogenerator - Junjun Huang; Wenlong Chen; Yuting Zong; Zhenming Chen; Honglin Li; Ning Zhang; Chengmei Gui; Xin Jiang (Chemical Engineering Journal, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Impact of stochastic collisions on cloud droplet number concentration and relative dispersion during Meiyu frontal system - Jingxi Sun; Chunsong Lu; Yan Yin; Sinan Gao; Junjun Li; Yiwei Zhang (Atmospheric Research, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Mixed vineyard prunings and sheep manure compost: Creating changes in vineyard soil dominant microbiota to impact fruit quality - Qian Tu; Yuanyuan Li; Weikang Ding; Shubo Zhou; Yanping Huang; Shiqiu Liu; Xuwu Min; Jiarui Zhang; Junjun Li; Chunlong Yuan (Applied Soil Ecology, 2025)

Optimization Strategy for Container Transshipment Between Yards at U-Shaped Sea-Rail Intermodal Terminal - Zeyi Liu; Junjun Li (Journal of Marine Science and Engineering, 2025)
The U-shaped automated container terminal (U-ACT) meets the requirements of sea-rail intermodal transportation with its unique layout. However, this layout also presents challenges, such as complex container transshipment planning and challenging equipment scheduling, which limit further improvements in overall efficiency. This paper focuses on the integrated scheduling of horizontal transportation and container-handling equipment for container transshipment at U-ACT. To minimize operation time and energy consumption while addressing path conflicts among container trucks, we designed a two-layer scheduling model to generate an optimal scheduling scheme for each automated device. Given the complexity of the problem, we developed a reinforcement learning-driven hyper-heuristic algorithm (RLHA) capable of efficiently searching for near-optimal solutions. Small-scale experiments demonstrate that our RLHA outperforms other algorithms, improving optimization results by 5.14% to 28.87% when the number of container operation tasks reaches 100. Finally, large-scale experiments were conducted to analyze key factors impacting sea-rail intermodal transport operations at U-ACT, providing a foundation for practical optimization.

Delay Propagation at U-Shaped Automated Terminals for Multilevel Handlings Based on Multivariate Transfer Entropy - Xinyu Guo; Junjun Li; Bowei Xu (Journal of Marine Science and Engineering, 2025)
Port congestion leads to frequent delays in multilevel handlings at automated terminals (ATMH). These delays propagate throughout the terminal, intensified by the interdependencies among equipment, which severely undermines the overall efficiency of the port. To elucidate the characteristics of ATMH and to investigate the dynamics of delay propagation, this study employs causal analysis methods applied to a U-shaped automated terminal multilevel handling system. By integrating the Minimum Redundancy Maximum Relevance (mRMR) algorithm with multivariate transfer entropy, we propose a novel approach to develop an interactive influence network for a U-shaped automated container terminal. Furthermore, this research develops a delay propagation model that accounts for equipment withdrawal mechanisms. The simulation results indicate that the multilevel handling system exhibits a certain degree of randomness, with close interaction between Automated Guided Vehicles and yard cranes. Measures that involve the withdrawal of propagating equipment and the implementation of immunity control on critical equipment can significantly mitigate the spread of delays. This study broadens the methodological framework for existing research on multilevel handling systems at automated terminals, exploring the operational characteristics and propagation patterns of delays. Such insights will assist terminals in implementing effective governance strategies when confronted with delays induced by uncertain factors, thereby reducing the risk of delay propagation and enhancing overall operational efficiency.

Incartrilactones A and B: Two schinortriterpenoids with a 14,15-seco-15,17-cyclolancifoartane skeleton from Schisandra incarnata - Ying Gao; Juan Chen; Junjun Liu; Zijian Huang; Xiaogang Peng; Wanpeng Li; Chunlun Qin; Hanli Ruan (Phytochemistry, 2025)

Pea power against microbes: Elucidating the characteristics and antimicrobial mechanisms of antimicrobial peptides obtained through enzymatic hydrolysis of pea protein isolate - Jiake Wang; Tongliang Yang; Wenwen Yu; Junjun Zhou; Yaqing Bian; Shuhong Li; Ye Chen (Food Bioscience, 2025)

Bayesian optimization-based intensity measures for seismic assessment of structural systems in the near-fault region - Mingke Li; Junjun Guo; Zhongguo Guan (Engineering Structures, 2025)

Self-Assembled Arachidonic Acid Nanomicelles for Radiation-Induced Ferroptosis to Enhance Tumor Radioimmunotherapy - Jiadong Wang; Yueyue Jing; Li Liu; Pengfei Xing; Zheng Deng; Yifan Zhang; Xirui Wu; Bin Hu; Cai Zhang; Xianglong Sun; Yuqian Liu; Jiawei Liu; et al. (Chemical Engineering Journal, 2025)

Coupling effect of moisture desorption and matrix contraction on resistivity of water-bearing coal under high geothermal environment - Junjun Feng; Yuanfang Qu; Shigeng Li; Chuanhua Xu; Yankun Ma; Qisong Huang; Long Dang (Journal of Applied Geophysics, 2025)

Lemon-derived carbon quantum dots incorporated guar gum/sodium alginate films with enhanced the preservability for blanched asparagus active packaging - Jianing Zhang; Junjun Zhang; Xiaowei Huang; Xiaodong Zhai; Zhihua Li; Jiyong Shi; Remah Sobhy; Ibrahim Khalifa; Xiaobo Zou (Food Research International, 2025)

Hydration and solution properties of fluorescently labeled wheat arabinoxylans following enzymatic hydrolysis - Jieya Wang; Yan Liu; Qingbin Guo; Junjun Li; Liang Zou; Xinzhong Hu (Food Hydrocolloids, 2025)

Distribution characteristics, source analysis and ecological risk assessment of PAHs in tea garden soil in China - Jinzhi Li; Jiantao Xue; Yan Tan; Mingmin Jia; Junjun Feng; Xueqing Feng; Ningguo Zheng; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

Versatile inulin/trans-ferulic acid/silk sericin nanoparticles-nourished probiotic complex with prolonged intestinal retention for synergistic therapy of inflammatory bowel disease - Yujie Zhang; Xiaojiang Zhang; Lianxi Lv; Sheng Gao; Xiang Li; Ruochen Wang; Pengqian Wang; Feiyu Shi; Junjun She; Ya Wang (Carbohydrate Polymers, 2025)

Trust rebuilding through village co-construction - Junjun Li; Luan Chen; Ye Long; Jin Wang; Xun Li (Journal of Rural Studies, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Unveiling the role of intrinsic defects in N/S Co-Doped hard carbon for superior sodium-ion batteries - Yunlei Yang; Chang Liu; Junjun Yao; Zhenqi Tang; Ying Sun; Kun Zhang; Hui Li; Tianyi Ma; Jieshan Qiu (Chemical Engineering Journal, 2025)

Mechanistic insight of fungal–microalgal pellets in photobioreactor for heavy-metal wastewater bioremediation - Junjun Wang; Qinghua Tian; Jue Kang; Hao Zhou; Xinyi Yu; Guanzhou Qiu; Li Shen (Bioresource Technology, 2025)

Distinctive Neural Substrates of low and high Risky Decision Making: Evidence from the Balloon Analog Risk Task - Zhenlan Jin; Simeng Li; Changan Wang; Xiaoqian Chai; Junjun Zhang; Ling Li (Brain Topography, 2025)

Study on strengthened the Cd(II) adsorption based on co-culture of fungi and cyanobacteria - Linlin Cui; Junjun Wang; Xueling Wu; Jiaokun Li; Weimin Zeng; Guanzhou Qiu; Li Shen (Algal Research, 2025)

Silicon alleviates aluminum toxicity by promoting citrate secretion and reducing aluminum accumulation in the cell wall of soybean roots - Junjun Huang; Ruoyi Wang; Ying Wang; Yiwei Chen; Huanan Li; Huahua Wang (Acta Physiologiae Plantarum, 2025)

Periodically asymmetric responses of deep chlorophyll maximum to light and thermocline in a clear monomictic lake: Insights from monthly and diel scale observations - Jingyi Li; Qichao Zhou; Yue Dao; Di Song; Zhirong Yu; Junjun Chang; Erik Jeppesen (Science of The Total Environment, 2024)

Fine mapping and candidate gene mining of QSc/Sl.cib-7H for spike compactness and length and its pleiotropic effects on yield-related traits in barley (Hordeum vulgare L.) - Jinhui Wang; Yanyan Tang; Jin Li; Juanyu Zhang; Furong Huang; Qiang Li; Baowei Chen; Li’ao Zhang; Tao Li; Haili Zhang; Junjun Liang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2024)

Two genes encoding a bacterial-type ABC transporter function in aluminum tolerance in soybean - Junjun Huang; Huanan Li; Yiwei Chen; Xiaoyu Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Huahua Wang (Plant Cell Reports, 2024)

Macrophage migration inhibitory factor reversed senescent phenotype in human chondrocytes in vitro - Zhenlan Fu; Qingqing Li; Peiyao Jiang; Xiongbo Song; Junjun Yang; Guangxing Chen; Xiaoyuan Gong; Liu Yang (Molecular Biology Reports, 2024)

Silicon alleviates aluminum-induced programmed cell death through regulating the antioxidant defenses in soybean roots - Yuanyuan Yu; Ying Wang; Huanan Li; Yiwei Chen; Junjun Huang; Huahua Wang (Biologia, 2024)

Deformation characteristics of root-reinforced soil under traffic induced cyclic loading - Shusen Liu; Jun Li; Shumin Lyu; Yi Fang; Xiaodong JI; Junjun Ni (Transportation Geotechnics, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

Evaluation of pool-and-weir fishway efficiency for the upstream spawning migration of Qinghai Lake's naked carp - Senfan Ke; Elsa Goerig; Kaiwen Pang; Huaiyao Ji; Dongqing Li; Jiawei Xu; Junjun Tan; Hongfang Qi; Xiaotao Shi (Ecological Engineering, 2024)

Dissecting the mechanism of synergistic interactions between Aspergillus fumigatus and the microalgae Synechocystis sp. PCC6803 under Cd(II) exposure: insights from untargeted metabolomics - Li Shen; Jue Kang; Junjun Wang; Shiyu Shao; Hao Zhou; Xinyi Yu; Min Huang; Weimin Zeng (Journal of Hazardous Materials, 2024)

Microenvironment design strategies for enhanced CO2 electroreduction with a 60% full-cell energy efficiency - Pengtao Yue; Junjun Wu; Chaozhong Qin; Bowen Shi; Yang Wang; Yue Zhang; Yanan Zou; Jun Li; Liang Zhang; Xun Zhu; Miao Zhong; Qian Fu; et al. (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Optimizing growth and antioxidant function in heat-stressed broilers with vitamin C and betaine supplementation - Yan Li; Junjun Yuan; Shiang Sun; Feiyang Ma; Yongjie Xiong; Shaojun He (International Journal of Biometeorology, 2024)

Analysis of the critical parameters for tritiated water entrained moist gas emission from nuclear power station - Xi Xu; Kefeng Lv; Yang Li; Xudan Ma; Hualei Jiang; Chunhua Chen; Junjun Zhang (Annals of Nuclear Energy, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Combining metabolomics and transcriptomics to analyze key response metabolites and molecular mechanisms of Aspergillus fumigatus under cadmium stress - Qinghua Tian; Junjun Wang; Shiyu Shao; Hao Zhou; Jue Kang; Xinyi Yu; Min Huang; Guanzhou Qiu; Li Shen (Environmental Pollution, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

High acidity notably influences acid mine drainage treatment performance in constructed wetlands packed with composite organic substrates by affecting both abiotic and biotic routes - Deshou Cun; Shengjiong Deng; Xuan Li; Fan Yang; Junjun Chang; Pengchang Duan; Changqun Duan (Chemical Engineering Journal, 2024)

Experimental and theoretical study on performance of Cu-Fe spinel supported with certain inerts during chemical looping combustion - Yu Li; Li Wang; Daifen Chen; Jing Liu; Wei Fan; Junjun Sun (Chemical Engineering Journal, 2024)

Optimization and mechanism studies for the biosorption of rare earth ions by Yarrowia lipolytica - Li Shen; Xinyi Yu; Hao Zhou; Junjun Wang; Hongbo Zhao; Guanzhou Qiu; Zhu Chen (Environmental Science and Pollution Research, 2024)

Blood–Brain Barrier Permeability is Affected by Changes in Tight Junction Protein Expression at High-Altitude Hypoxic Conditions—this may have Implications for Brain Drug Transport - Guiqin Liu; Qian Wang; Lu Tian; Mengyue Wang; Delong Duo; Yabin Duan; Yue Lin; Junjun Han; Qiangqiang Jia; Junbo Zhu; Xiangyang Li (The AAPS Journal, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Evaluation of machine learning-dynamical hybrid method incorporating remote sensing data for in-season maize yield prediction under drought - Yi Luo; Huijing Wang; Junjun Cao; Jinxiao Li; Qun Tian; Guoyong Leng; Dev Niyogi (Precision Agriculture, 2024)

Recognition and Prediction of Multi-Level Handling Complexity at Automated Terminals Based on ARIMA - Yong Ma; Junjun Li (Journal of Marine Science and Engineering, 2024)
Accurate recognition and prediction of the multi-level handling complexity in automated container terminals (referred to as “automated terminals”) is a prerequisite for improving the effectiveness of scheduling and realizing intelligent operation and maintenance. According to the operating characteristics of the automated terminal equipment, the operating network is constructed of automated terminals that describe the characteristics of operating complexity. We use K-medoids and a light gradient boosting machine (LightGBM) to construct a K-LightGBM model that recognizes multi-level handling complexity. The key lies in the reasonable construction of prediction models. A hyper-heuristic autoregressive integrated moving average (ARIMA) model is proposed to address the problem that the ARIMA is ineffective in predicting nonlinear data. We combine ARIMA and the LightGBM model to establish an ARIMA-LightGBM model to predict multi-level handling and residuals. To improve accuracy, we propose the two residual prediction strategies of direct prediction and limited residual boundary prediction based on the residuals generated by ARIMA. We propose a hyper-heuristic algorithm based on a gradient descent-trust region (GD-TR) to compute the weights of predicted values under the two strategies, which improves the global search capability by GD and TR. The particle swarm optimization algorithm, simulated annealing algorithm, and ant colony optimization algorithm are low-level heuristics. Simulation results show that the proposed model possesses the lowest root mean square error on all characteristics compared to ARIMA, E-ARIMA, and ARIMA-LSTM. Therefore, the proposed model is very effective in improving the accuracy of predicting the multi-level handling complexity at automated terminals.

Evaluation of biological activity and prebiotic properties of proanthocyanidins with different degrees of polymerization through simulated digestion and in vitro fermentation by human fecal microbiota - Xiaoyi Chen; Shuai Liu; Hong Song; Chunlong Yuan; Junjun Li (Food Chemistry, 2024)

Optimizing a Rock-Like Material Mix Design for Enhancing the Mining Fracture Monitoring Accuracy of Borehole Resistivity Method - Yuben Liu; Zhu Gao; Junjun Jiao; Mohammad Waqar Ali Asad; Michael Hitch; Danqi Li (Rock Mechanics and Rock Engineering, 2024)

Path analysis of digital development on the green industrial transformation of Chinese resource-based enterprises - Qi Zhao; Ming Guo; Fangfang Feng; Junjun Li; Hangtian Guan (Resources Policy, 2024)

Micro/nanoplastic pollution heterogeneously increased greenhouse gas emissions from wetlands: A multilevel meta-analysis - Yun Zhou; Deshou Cun; Haoyu Wang; Yanye Li; Junjun Chang (Journal of Cleaner Production, 2024)

Preparation of active film based on cinnamon essential oil into β-cyclodextrin with high hydrophobic and its preservation for griskin - Yefeng Guan; Junjun Zhang; Jianing Zhang; Wenjun Song; Jiyong Shi; Xiaowei Huang; Xiaodong Zhai; Di Zhang; Zhihua Li; Xiaobo Zou (Food Control, 2024)

Transient anoxic conditions boost N2O emissions by stimulating denitrification capacity and decreasing N2O reduction ratio in soils with different carbon substrates - Shan Zhuang; Junjun Ding; Wei Lin; Qian Zheng; Xinyue Kou; Qiaozhen Li; Chunying Xu; Lili Mao; Yanshuo Pan; Ying Gao; Dongfei Han; Yuzhong Li (Soil Biology and Biochemistry, 2024)

Phosphate-solubilizing bacteria improve the antioxidant enzyme activity of Potamogeton crispus L. and enhance the remediation effect on Cd-contaminated sediment - Yuxin Cheng; Junjun Yuan; Gongting Wang; Zhenzhen Hu; Wenqing Luo; Xin Zhao; Yali Guo; Xiaonan Ji; Wei Hu; Min Li (Journal of Hazardous Materials, 2024)

Co-sputtering construction of Gd-doped WO3 nano-stalagmites film for bi-funcional electrochromic and energy storage applications - Yi Yin; Yiwen Zhu; Pengkun Liao; Xiaoyi Yuan; Junjun Jia; Changyong Lan; Chun Li (Chemical Engineering Journal, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Containership delay propagation risk analysis based on effective multivariate transfer entropy - Junjun Li; Shuo Zhang; Bowei Xu (Ocean Engineering, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Structure, stability and in vitro digestion of a novel zein-based oil gel delivery system loaded β-carotene - Siqi Qiang; Junjun Zhou; Tongliang Yang; Jiake Wang; Ye Chen; Guiyun Chen; Shuhong Li (Journal of Food Engineering, 2024)

Metabolomics-based analysis of the interaction effects and stress response mechanisms in the co-culture system of fungi and microalgae under cadmium stress - Junjun Wang; Qinghua Tian; Jue Kang; Hao Zhou; Xinyi Yu; Guanzhou Qiu; Li Shen (Journal of Cleaner Production, 2024)

Carbon felt (CF) acted as an “ionic capacitor” to enhance flow electrode capacitive deionization (FCDI) desalination performance - Yunke Li; Junjun Ma; Minghao Yu; Jianrui Niu; Jiarong Gu; Meng Chen; Puming Zhang; Jing Zhang; Chun Liu (Desalination, 2024)

Effects of acetyl groups on the prebiotic properties of glucomannan extracted from Artemisia sphaerocephala Krasch seeds - Haocheng Li; Gongda Wang; Ximei Yan; Xinzhong Hu; Junjun Li (Carbohydrate Polymers, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

Physiological regulation of microalgae under cadmium stress and response mechanisms of time-series analysis using metabolomics - Junjun Wang; Qinghua Tian; Hao Zhou; Jue Kang; Xinyi Yu; Guanzhou Qiu; Li Shen (Science of The Total Environment, 2024)

9,9′-epoxylignans from Syringa pinnatifolia: A typical case of stereochemical assignment by a quantum chemical calculation with MAEΔΔ parameter - Shungang Jiao; Changxin Liu; Panlong Chen; Junjun Li; Jingjing Sun; Xiaoli Gao; Xingyun Chai (Phytochemistry, 2024)

Comparison of biosorption behavior and mechanism of La3+, Sm3+, Y3+, Nd3+, Er3+ by Aspergillus niger and Bacillus sp - Hao Zhou; Junjun Wang; Shiyu Shao; Xinyi Yu; Jue Kang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Water Process Engineering, 2024)

Reassessing the greenhouse effect of biogenic carbon emissions in constructed wetlands - Liping Hu; Ziqian Li; Lingwei Kong; Jun Wei; Junjun Chang; Wenqing Shi (Journal of Environmental Management, 2024)

Techno-economic assessment of retrofitting indirect-heated calcium looping using coal and biomass as fuels into an existing cement plant for CO2 capture - Junjun Yin; Chao'en Li; Gabriel Paicu; Shi Su (Gas Science and Engineering, 2024)

Experimental study on a cable-stayed bridge isolated with the combination of elastoplastic cables and fluid viscous dampers in the transverse direction - Junjun Guo; Mingke Li; Yongmu Wu; Yifeng Xiao; Zhongguo Guan (Engineering Structures, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

Fine classification of rice paddy using multitemporal compact polarimetric SAR C band data based on machine learning methods - Xianyu Guo; Junjun Yin; Kun Li; Jian Yang; Huimin Zou; Fukun Yang (Frontiers of Earth Science, 2024)

Combined treatment with pre-aeration and carrier addition strengthens the purification performance of a deep pilot-scale duckweed-based pond - Yonggui Zhao; Jinquan Li; Yuejiao Yang; Ruidong Ma; Ying Peng; Xiaoyun Sun; Siwei Gao; Junjun Chang; Changqun Duan (Journal of Water Process Engineering, 2024)

Numerical investigation on NO formation of staged oxy-fuel combustion in a 35 MW large pilot boiler - Junjun Guo; Teng Guo; Tai Zhang; Fan Hu; Pengfei Li; Zhaohui Liu (Fuel, 2024)

A ratiometric fluorescence amine sensor based on carbon quantum dot-loaded electrospun polyvinylidene fluoride film for visual monitoring of food freshness - Wenjun Song; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Yuhong Xue; Yue Sun; Wei Sun; Junjun Zhang; Xiaowei Huang; Zhihua Li; Tingting Shen; Yanxiao Li; et al. (Food Chemistry, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Shake table test and numerical model update for a viscous damper isolated cable-stayed bridge - Junjun Guo; Mingke Li; Yongmu Wu; Yifeng Xiao; Zhongguo Guan (Soil Dynamics and Earthquake Engineering, 2024)

Trends in global ambient fine particulate matter pollution and diabetes mortality rates attributable to it in the 1990–2019: 30 years systematic analysis of global burden of disease - Junjun Ye; Jilin Li; Liping Li; Shuo Zhang; Jingxian Chen; Dan Zhu; Chuanyan Zhang; Bin Xie; Bangzhou Zhang; Kaijian Hou (Science of The Total Environment, 2024)

Response of growth performance and cecum microbial community to cyclic heat stress in broilers - Junjun Yuan; Yan Li; Shiang Sun; Jiaying Wu; Jin Zhou; Shaojun He (Tropical Animal Health and Production, 2024)

cTBS to Right DLPFC Modulates Physiological Correlates of Conflict Processing: Evidence from a Stroop task - Ping Xu; Song Wang; Yulu Yang; Bishal Guragai; Qiuzhu Zhang; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Topography, 2024)

The Probability Density Function Related to Shallow Cumulus Entrainment Rate and Its Influencing Factors in a Large-Eddy Simulation - Lei Zhu; Chunsong Lu; Xiaoqi Xu; Xin He; Junjun Li; Shi Luo; Yuan Wang; Fan Wang (Advances in Atmospheric Sciences, 2024)

Integrated vegetation cover of typical steppe in China based on mixed decomposing derived from high resolution remote sensing data - Junjun Wu; Yi Li; Bo Zhong; Qinhuo Liu; Shanlong Wu; Changyuan Ji; Jing Zhao; Li Li; Xiaoliang Shi; Aixia Yang (Science of The Total Environment, 2023)

The incidence of asthma attributable to temperature variability: An ecological study based on 1990–2019 GBD data - Qingsong Xu; Qinfeng Zhou; Junjun Chen; Tong Li; Junxiong Ma; Runming Du; Mintao Su; Jing Li; Ming Xu; Shengzhi Sun; Jing Ma; Murugappan Ramanathan; et al. (Science of The Total Environment, 2023)

Small molecule linoleic acid inhibiting whey syneresis via interact with milk proteins in the fermentation of set yogurt fortified with c9,t11-conjugated linoleic acid - Junjun Qing; Cheng Peng; Hongbing Chen; Haixing Li; Xiaohua Liu (Food Chemistry, 2023)

First identification and molecular subtyping of Blastocystis in free-living wild birds from urban Xinxiang, China - Tiantian Li; Huimei Feng; Yingxu Zheng; Junjun Lv; Chi Zhang; Xuefeng Yang; Xuehan Liu (Veterinary Research Communications, 2023)

Knowledge, Attitude, and Practice of Breast Cancer Patients Toward Lymphedema Complications: Cross-Sectional Study - Yan Qin; Junjun Lu; Shanze Li; Jie Huang; Wenjing Teng; Yue Wu; Wanqing Chen; Lizhen Wang; Weikang Zhu (Journal of Cancer Education, 2023)

Potential role of selenium in alleviating obesity-related iron dyshomeostasis - Guanwen Liu; Junjun Li; Bing Pang; Yinghui Li; Fengqin Xu; Ning Liao; Dongyan Shao; Chunmei Jiang; Junling Shi (Critical Reviews in Food Science and Nutrition, 2023)

Increasing amounts of midwestern Tibetan Plateau vortices and their response to soil moisture distribution coupled with different synoptic systems - Yuxin Kuang; Jie Zhang; Zishu Miao; Zhiheng Chen; Junjun Li; Miaomiao Niu; Shiying Wu; Rui Hu (International Journal of Climatology, 2023)
Tibetan Plateau Vortices (TPVs) are important synoptic systems that affect precipitation over the Tibetan Plateau (TP) and downstream weather. By using daily reanalysis data provided by ECMWF and the objective identification methods, the study identified the basic spatiotemporal changes of TPVs, clustered the TPVs by different dynamic circulation types and explored the dynamic circulation background of the classified TPVs in the midwestern TP and their relationship with thermal factors, such as sensible heat and soil moisture. The results show that TPVs in the midwestern TP exhibited an increasing trend from May to August, resulting from the coupling of dynamics with thermal forcing. The related synoptic circulations were divided into four types according to the dynamic circulations: the shortwave trough, the longwave trough, the shear line and the plateau anticyclone type. Among the TPVs, the percentage of TPVs in the shortwave and longwave trough type was relatively large, accounting for 48.7% and 31.5%, respectively, both of which were dominated by the coupling of increased sensible heat and decreased soil moisture. The shear line type was less affected by thermal factors, and mainly driven by dynamic factors, whereas the soil moisture gradient was responsible for the plateau anticyclone type. The simulation experiment also proved this conclusion.

Cotton yield stability achieved through manipulation of vegetative branching and photoassimilate partitioning under reduced seedling density and double seedlings per hole - Jingyuan Zhou; JunJun Nie; Xiangqiang Kong; Jianlong Dai; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Ziqing Hua; Zhenhuai Li; Hezhong Dong (Field Crops Research, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Super-strong Zn and S atomic terminals in an organic/inorganic hybrid S-scheme polyimide based heterojunction for efficient photocatalytic treatment of mixed pollutant wastewater - Siyi Li; Yushu Wang; Hongli An; Junjun Lin; Shuang Jiang; Tianyong Zhang; Bin Li (Chemical Engineering Journal, 2023)

Utilization of Aspergillus niger strain to leach rare earth elements based on untargeted metabolomics analysis - Hao Zhou; Xinyi Yu; Junjun Wang; Guanzhou Qiu; Hongbo Zhao; Li Shen (Chemical Engineering Journal, 2023)

Key metabolites and regulatory network mechanisms in co-culture of fungi and microalgae based on metabolomics analysis - Junjun Wang; Qinghua Tian; Hao Zhou; Jue Kang; Xinyi Yu; Li Shen (Bioresource Technology, 2023)

Characterization and sources of water-soluble organic species in PM2.5 in a remote mountain environment in Southeastern China - Jun Tao; Zhisheng Zhang; Leiming Zhang; Yunfei Wu; Yanqin Ren; Jiawei Li; Junjun Huang; Gehui Wang; Zhenxin Shen; Renjian Zhang; Boguang Wang (Atmospheric Environment, 2023)

Gut microbiota bridges dietary nutrients and host immunity - Lijuan Fan; Yaoyao Xia; Youxia Wang; Dandan Han; Yanli Liu; Jiahuan Li; Jie Fu; Leli Wang; Zhending Gan; Bingnan Liu; Jian Fu; Congrui Zhu; et al. (Science China Life Sciences, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Adaptive sliding mode controller combined with pseudo-inverse-based thruster allocator design for ROV with variable coefficients - Xinyang Li; Hao Wen; Junjun Cao; Baoheng Yao; Lian Lian; Zhihua Mao (Ocean Engineering, 2023)

Biofilm formation and development during the pyrite bioleaching of moderately thermophilic microorganisms - Li Shen; Jinju Cheng; Junjun Wang; Yejuan Zhang; Hao Zhou; Xueling Wu; Jiaokun Li; Weiming Zeng (Hydrometallurgy, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

Alternate intercropping of cotton and peanut increases productivity by increasing canopy photosynthesis and nutrient uptake under the influence of rhizobacteria - Baojie Chi; Jin Liu; Jianlong Dai; Zhenhuai Li; Dongmei Zhang; Shizhen Xu; Junjun Nie; Sumei Wan; Cundong Li; Hezhong Dong (Field Crops Research, 2023)

Reducing uncertainties in hydromechanical modeling with a recently developed Rosetta 3 podeotransfer function - Wei Shao; Sijie Chen; Meijun Li; Ye Su; Junjun Ni; Jianzhi Dong; Yonggen Zhang; Zongji Yang (Engineering Geology, 2023)

The Regulatory Mechanism of Rab21 in Human Diseases - Xinjian Li; Junjun Ni; Hong Qing; Zhenzhen Quan (Molecular Neurobiology, 2023)

High contribution of new particle formation to ultrafine particles in four seasons in an urban atmosphere in south China - Li Tao; Zhen Zhou; Jun Tao; Leiming Zhang; Cheng Wu; Jiawei Li; Dingli Yue; Zhijun Wu; Zhisheng Zhang; Ziyang Yuan; Junjun Huang; Boguang Wang (Science of The Total Environment, 2023)

Phase-mediated mercury removal from water using multilayered molybdenum disulfide: The key role of redox mechanism - Jia Sun; Junjun Pei; Zhiyuan Qiu; Jing Guo; Bo Li; Kaixing Fu; Kai Yin; Shenglian Luo (Journal of Cleaner Production, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

Observational study of relationships between entrainment rate, homogeneity of mixing, and cloud droplet relative dispersion - Chunsong Lu; Lei Zhu; Yangang Liu; Fan Mei; Jerome D. Fast; Mikhail S. Pekour; Shi Luo; Xiaoqi Xu; Xin He; Junjun Li; Sinan Gao (Atmospheric Research, 2023)

The reduced Siberian spring snow cover modulation on southward northernmost margin of East Asia summer monsoon - Shiying Wu; Jie Zhang; Junjun Li; Zhiheng Chen; Yun Hang; Miaomiao Niu; Yuxin Kuang; Rui Hu (Climate Dynamics, 2023)

Urbanization shifts long‐term phenology and severity of phytoplankton blooms in an urban lake through different pathways - Yuanrui Li; Juan Tao; Yunlin Zhang; Kun Shi; Junjun Chang; Min Pan; Lirong Song; Erik Jeppesen; Qichao Zhou (Global Change Biology, 2023)
Climate change can induce phytoplankton blooms (PBs) in eutrophic lakes worldwide, and these blooms severely threaten lake ecosystems and human health. However, it is unclear how urbanization and its interaction with climate impact PBs, which has implications for the management of lakes. Here, we used multi‐source remote sensing data and integrated the Virtual‐Baseline Floating macroAlgae Height (VB‐FAH) index and OTSU threshold automatic segmentation algorithm to extract the area of PBs in Lake Dianchi, China, which has been subjected to frequent PBs and rapid urbanization in its vicinity. We further explored long‐term (2000–2021) trends in the phenological and severity metrics of PBs and quantified the contributions from urbanization, climate change, and also nutrient levels to these trends. When comparing data from 2011–2021 to 2000–2010, we found significantly advanced initiation of PBs (28.6 days) and noticeably longer duration (51.9 days) but an insignificant trend in time of disappearance. The enhancement of algal nutrient use efficiency, likely induced by increased water temperature and reduced nutrient concentrations, presumably contributed to an earlier initiation and longer duration of PBs, while there was a negative correlation between spring wind speed and the initiation of PBs. Fortunately, we found that both the area of the PBs and the frequency of severe blooms (covering more than 19.8 km 2 ) demonstrated downward trends, which could be attributed to increased wind speed and/or reduced nutrient levels. Moreover, the enhanced land surface temperature caused by urbanization altered the thermodynamic characteristics between the land and the lake, which, in turn, possibly caused an increase in local wind speed and water temperature, suggesting that urbanization can differently regulate the phenology and severity of PBs. Our findings have significant implications for the understanding of the impacts of urbanization on PB dynamics and for improving lake management practices to promote sustainable urban development under global change.

Land use regulates the spectroscopic properties and sources of dissolved organic matter in the inflowing rivers of a large plateau lake in southwestern China: implication for organic pollution control - Rong Wu; Weijie Guo; Yutong Li; Shengjiong Deng; Junjun Chang (Environmental Science and Pollution Research, 2023)

Quantitative assessment of the effects of zeolite alteration processes on deep clastic reservoirs – A case study of the Jiamuhe Formation in the Shawan Sag, Junggar Basin, China - Junjun Zhou; Haiguang Wu; Jian Wang; Guang Hu; Yunfeng Zhang; Jinlai Feng; Yilin Li (Marine and Petroleum Geology, 2023)

Vertical effects of near-fault ground motions and the optimal IMs for seismic response of continuous girder bridges with FPB isolators - Mingke Li; Junjun Guo; Penghui Zhang; Zhongguo Guan (Engineering Structures, 2023)

The role of middle frontal gyrus in working memory retrieval by the effect of target detection tasks: a simultaneous EEG-fMRI study - Ping Xu; Min Wang; Tingting Zhang; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Structure and Function, 2023)

Gut microbiota as a potential target for developing anti-fatigue foods - Yinghui Li; Junjun Li; Fengqin Xu; Guanwen Liu; Bing Pang; Ning Liao; Huixin Li; Junling Shi (Critical Reviews in Food Science and Nutrition, 2023)

Air conditioning system with dual-temperature chilled water for air grading treatment in data centers - Wentao Wang; Chenjiyu Liang; Fuhai Zha; Huan Wang; Wenxing Shi; Zhiyong Cui; Kaiqing Zhang; Hunlin Jia; Junjun Li; Xianting Li (Energy and Buildings, 2023)

Effects of personal carbon trading scheme on consumers' new energy vehicles replacement decision: An economic trade-off analysis - Jun Li; Lili Gao; Xianfeng Hu; Junjun Jia; Shanyong Wang (Environmental Impact Assessment Review, 2023)

Changes in soil organic carbon stability in association with microbial carbon use efficiency following 40 years of afforestation - Qianxi Li; Wei Jia; Junjun Wu; Lingling Wang; Feng Huang; Xiaoli Cheng (CATENA, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Structural and functional neural substrates underlying the concreteness effect - Jing Yan; Wenjuan Li; Tingting Zhang; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Structure and Function, 2023)

Using modular connectome-based predictive modeling to reveal brain-behavior relationships of individual differences in working memory - Huayi Yang; Junjun Zhang; Zhenlan Jin; Pouya Bashivan; Ling Li (Brain Structure and Function, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Synthesis of a micro-nano FeOx/MnOx modified large volume non-enamel ceramsites for selective and efficient adsorption of cadmium - Junkang Guo; Xianwei Yu; Muhammad Haris; Tian Liu; Jiayuan Wang; Junjun Zhao; Yifan Li; Chao Zhang (Journal of Environmental Chemical Engineering, 2023)

A visual bi-layer indicator based on mulberry anthocyanins with high stability for monitoring Chinese mitten crab freshness - Xiaowei Huang; Liuzi Du; Zhihua Li; Jin Xue; Jiyong Shi; Haroon Elrasheid Tahir; Xiaodong Zhai; Junjun Zhang; Ning Zhang; Wei Sun; Xiaobo Zou (Food Chemistry, 2023)

A non-thermal modification method to enhance the encapsulation efficiency, stability, and slow-release performance of zein-based delivery systems – Cold plasma - Junjun Zhou; Yaqing Bian; Tongliang Yang; Jiake Wang; Tianai Kong; Yifu Zhang; Ye Chen; Shuhong Li (Journal of Food Engineering, 2023)

Multiple biological activities and biosynthesis mechanisms of specific conjugated linoleic acid isomers and analytical methods for prospective application - Suhong Li; Liangwei Xu; Junjun Qing; Xiaodan Wu; Haixing Li; Hongbing Chen; Xiaohua Liu (Food Chemistry, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

Enhanced VFAs production from microalgal hydrolytic acidification with ultrasonic-alkali pretreatment - Liwen Zhang; Jingjing Yang; Bingdang Wu; Junjun Liu; Xiaoyi Xu; Wei Wu; Jinlong Zhuang; Hanxiang Li; Tianyin Huang (Algal Research, 2023)

Resilience Regulation Strategy for Container Port Supply Chain under Disruptive Events - Bowei Xu; Weiting Liu; Junjun Li (Journal of Marine Science and Engineering, 2023)
There are many inevitable disruptive events, such as the COVID-19 pandemic, natural disasters and geopolitical conflicts, during the operation of the container port supply chain (CPSC). These events bring ship delays, port congestion and turnover inefficiency. In order to enhance the resilience of the CPSC, a modified two-stage CPSC system containing a container pretreatment system (CPS) and a container handling system (CHS) is built. A two-dimensional resilience index is designed to measure its affordability and recovery. An adaptive fuzzy double-feedback adjustment (AFDA) strategy is proposed to mitigate the disruptive effects and regulate its dynamicity. The AFDA strategy consists of the first-level fuzzy logic control system and the second-level adaptive fuzzy adjustment system. Simulations show the AFDA strategy outperforms the original system, PID, and two pipelines for improved dynamic response and augmented resilience. This study effectively supports the operations manager in determining the proper control policies and resilience management with respect to indeterminate container waiting delay and allocation delay due to disruptive effects.

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Thin sheets of bean curd treated by cold plasma: Changes in surface structure and physicochemical properties - Tongliang Yang; Yuhe Wang; Bowen Yang; Yifu Zhang; Jiake Wang; Siqi Qiang; Junjun Zhou; Shuhong Li; Ye Chen (Innovative Food Science & Emerging Technologies, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Computational identification and systematic classification of cytochrome P450 genes in Pogostemon cablin provide insights into flavonoids biosynthesis - Junjun Li; Cao Deng; Mengjia Liu; Yang He (Acta Physiologiae Plantarum, 2023)

Metagenomic analysis reveals patterns and hosts of antibiotic resistance in different pig farms - Bingzhen Ji; Junjun Qin; Yijia Ma; Xin Liu; Tian Wang; Guiming Liu; Bugao Li; Guoliang wang; Pengfei Gao (Environmental Science and Pollution Research, 2023)

Research on Multi-Equipment Cluster Scheduling of U-Shaped Automated Terminal Yard and Railway Yard - Junjun Li; Lixing Yan; Bowei Xu (Journal of Marine Science and Engineering, 2023)
A new layout of the U-shaped automated terminal is more convenient to connect between the terminal and the railway. In this study, a sort of cluster scheduling method for multiple equipment between a U-shaped automated terminal yard and a railway yard is proposed. The innovation points are as follows: (1) Considering that the rail gantry crane (RGC), intelligent guided vehicle (IGV), and double cantilever rail crane (DCRC) usually work in groups, they are grouped and cluster-scheduled. (2) A hybrid integer programming model is established to minimize container transit times, and non-crossing constraints and safe distance constraints are included to reflect complex interactions among terminal equipment. (3) An ADMM (Alternating Direction Method of Multipliers)-based framework is proposed to dualize the hard-edge constraints and break the cluster scheduling problem down into a specific subproblem set of RGCs, IGVs, and DCRCs, and their time cost is iteratively adjusted to improve the solution quality. The experiment results show that the solution of the proposed method, which can effectively avoid IGV conflict, is better than that of the standard Lagrange relaxation (LR) when the number of equipments participating in scheduling increases. This study on multi-equipment cluster scheduling is conducive to improving the collaborative handling and continuous work of terminal equipment, and improving the efficiency of the automated terminal and the sea–rail intermodal transport.

Diverse lignans with protective effect against hypoxia/oxidative injuries to H9c2 cells from Syringa pinnatifolia Hemsl. - Shungang Jiao; Xiaoli Gao; Junjun Li; Ruifei Zhang; Shana Wuken; Changxin Liu; Suyile Chen; Pengfei Tu; Luqi Huang; Xingyun Chai (Phytochemistry, 2023)

Influence of MnO2 crystal existing form on its catalytic performance for toluene oxidation - Xuxu Zhai; Luming Li; Shuang Song; Junjun Zhang; Jun Ma; Chongrui Xie; Wei Chu (Fuel, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

A novel framework for seismic fragility analysis with the combination of Box-Cox transformation and Bayesian inference - Junjun Guo; Penghui Zhang; Jingquan Wang; Shuai Li; Zhongguo Guan (Engineering Structures, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Fine particulate pollution driven by nitrate in the moisture urban atmospheric environment in the Pearl River Delta region of south China - Jun Tao; Junjun Huang; Guojian Bian; Leiming Zhang; Zhen Zhou; Zhisheng Zhang; Jiawei Li; Yucong Miao; Ziyang Yuan; Qinge Sha; Linhai Xiao; Boguang Wang (Journal of Environmental Management, 2023)

Modulating interfacial charge distribution of NiSe nanoarrays with NiFe-LDH nanosheets for boosting oxygen evolution reaction - Weiwei Bao; Chunming Yang; Taotao Ai; Junjun Zhang; Lihai Zhou; Yan li; Xueling Wei; Xiangyu Zou; Yong Wang (Fuel, 2023)

Study on cinnamon essential oil release performance based on pH-triggered dynamic mechanism of active packaging for meat preservation - Junjun Zhang; Jianing Zhang; Xiaowei Huang; Jiyong Shi; Arslan Muhammad; Xiaodong Zhai; Jianbo Xiao; Zhihua Li; Megan Povey; Xiaobo Zou (Food Chemistry, 2023)

Smart films of carbohydrate-based/sunflower wax/purple Chinese cabbage anthocyanins: A biomarker of chicken freshness - Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Li Lui; Junjun Zhang; Xiaodong Zhai; Amer Ali Mahdi; Nosyba A. Ibrahim; Gustav Komla Mahunu; Mahmoud M. Hassan; Zou Xiaobo; Shi Jiyong (Food Chemistry, 2023)

Spectrum and mortality of opportunistic infections among HIV/AIDS patients in southwestern China - Sirun Meng; Qiao Tang; Zhiman Xie; Nianning Wu; Yingmei Qin; Rongfeng Chen; Xiaoyu Chen; Xiu Chen; Yueqi Li; Minjuan Shi; Li Ye; Hao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
We describe the opportunistic infections (OIs) of HIV/AIDS to understand the spectrum, mortality, and frequency of multiple coinfected OIs among HIV/AIDS patients in southern China, where OIs are severe. We carried out a retrospective cohort study of hospitalized HIV-infected individuals at the Fourth People’s Hospital of Nanning, Guangxi, China, from Jan. 2011 to May. 2019. The chi-square test was used to analyze cross-infection; the Kaplan‒Meier analysis was used to compare mortality. A total of 12,612 HIV-infected patients were admitted to this cohort study. Among them, 8982 (71.2%) developed one or more OIs. The overall in-hospital mortality rate was 9.0%. Among the patients, 35.6% coinfected one OI, and 64.4% coinfected more than two OIs simultaneously. Almost half of the patients (60.6%) had CD4 + T-cell counts < 200 cells/μL. Pneumonia (39.8%), tuberculosis (35.3%), and candidiasis (28.8%) were the most common OIs. Coinfected cryptococcal meningitis and dermatitis are the most common combined OIs. The rate of anaemia (17.0%) was highest among those common HIV-associated complications. Multiple OIs are commonly found in hospitalized HIV/AIDS patients in southwestern China, which highlights the need for improved diagnosis and treatment.

Impacts of regional uplift of the Tibetan Plateau on local summer precipitation and downstream moisture budget: A simulation study - Kai Yang; Jinghua Chen; Chunsong Lu; Junjun Li; Tianyu Liu; Liping Deng; Yanwei Li (International Journal of Climatology, 2022)
Using the Weather Research and Forecasting (WRF) model, a series of sensitivity experiments were conducted to study the individual and overall effects of the various topographic uplifts of the Tibetan Plateau (TP) on regional climate variability. The presence of the southern slope of the TP facilitates the maintenance and development of the South Asia High (SAH), which produces a positive cyclic response between local precipitation and SAH, so that the northern branch of the South Asian summer monsoon (SASM) maintains the water vapor supply. At the same time, the southern slope of the TP has a positive effect on the mid‐latitude tropospheric anomalous cyclone and anticyclone systems which promotes the downstream advancement of the East Asian summer monsoon (EASM) and is favourable for the transfer of water vapor and convective clouds downstream. The role of the TP platform is mainly due to the lifting of moisture generated by its local heating, which favours the formation of local convective clouds and precipitation while causing nonadiabatic warming of the troposphere. Water vapor transported from the TP could affect precipitation in central‐eastern China (CEC). However, the supply of water vapor in Southern East China (SEC) mainly comes from the southeast coast of China. The Tibetan Plateau sensitive areas (TPSA) have impacts on the water vapor transport path. Removing the TPSA favours an increase in precipitation and convective clouds in SEC. The removal of topographic disturbances favours the convergence and dispersion of water vapor at mid‐latitudes. The mid‐latitude dynamical anomaly may form a standoff with the low‐latitude dynamical system. This leads to inefficient precipitation and convective generation processes, a weakened monsoon advance over land, and a southward shift in the rainfall belt.

Identification of PP2C Genes in Tibetan Hulless Barley (Hordeum vulgare var. nudum) Under Dehydration Stress and Initiatory Expression and Functional Analysis of HvPP2C59 - Junjun Liang; Ling Yi; Lilan Li; Haili Zhang; Yunshu Zhang; Guangbing Deng; Hai Long; Maoqun Yu (Plant Molecular Biology Reporter, 2022)

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Relationships between Cloud Droplet Spectral Relative Dispersion and Entrainment Rate and Their Impacting Factors - Shi Luo; Chunsong Lu; Yangang Liu; Yaohui Li; Wenhua Gao; Yujun Qiu; Xiaoqi Xu; Junjun Li; Lei Zhu; Yuan Wang; Junjie Wu; Xinlin Yang (Advances in Atmospheric Sciences, 2022)

Relationship between meteorological factors and mortality from respiratory diseases in a subtropical humid region along the Yangtze River in China - Lingxiang Yu; Junjun Zhu; Ming Shao; Jinian Wang; Yubo Ma; Kai Hou; Huijun Li; Jiansheng Zhu; Xiaoyun Fan; Faming Pan (Environmental Science and Pollution Research, 2022)

Visual Selective Attention P300 Source in Frontal-Parietal Lobe: ERP and fMRI Study - Qiuzhu Zhang; Cimei Luo; Ronald Ngetich; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Topography, 2022)

The critical role of the orbitofrontal cortex for regret in an economic decision-making task - Tingting Zhang; Qiuzhu Zhang; Jiaqi Wu; Min Wang; Wenjuan Li; Jing Yan; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Structure and Function, 2022)

Structural and functional MRI evidence for significant contribution of precentral gyrus to flexible oculomotor control: evidence from the antisaccade task - Zhenlan Jin; Dong-gang Jin; Min Xiao; Aolin Ding; Jing Tian; Junjun Zhang; Ling Li (Brain Structure and Function, 2022)
Antisaccade task requires inhibition of a prepotent prosaccade to a peripheral target and initiation of a saccade to the opposite location, and, therefore, is used as a tool to investigate behavioral adjustment. The frontal and parietal cortices are both known for their activation during saccade generation, but it is unclear whether their neuroanatomical characteristics also contribute to antisaccades. Here, we took antisaccade cost (antisaccade latency minus prosaccade latency) as an index for additional time for generating antisaccades. Fifty-eight participants conducted pro and antisaccade tasks outside the magnetic resonance imaging (MRI) scanner and their structural MRI (sMRI) data were also collected to explore brain regions neuroanatomically related to antisaccade cost. Then, twelve participants performed saccade tasks in the scanner and their task-state functional MRI (fMRI) data were collected to verify the activation of structurally identified brain regions during the saccade generation. Voxel-based morphometry (VBM) results revealed that gray matter volume (GMV) of the left precentral gyrus and the left insula were positively correlated with the antisaccade cost, which was validated by the prediction analysis. Brain activation results showed the activation of the precentral during both pro and antisaccade execution period, but not the insula. Our results suggest that precentral gyrus and insula play vital roles to antisaccade cost, but possibly in different ways. The insula, a key node of the salience network, possibly regulates the saliency processing of the target, while the precentral gyrus possibly mediates the generation of saccades. Our study especially highlights an outstanding role of the precentral gyrus in flexible oculomotor control.

Accuracy assessment and climatology of MODIS aerosol optical properties over North Africa - Abou Bakr Merdji; Xiaofeng Xu; Chunsong Lu; Birhanu Asmerom Habtemicheal; Junjun Li (Environmental Science and Pollution Research, 2022)

A Hybrid Dynamic Method for Conflict-Free Integrated Schedule Optimization in U-Shaped Automated Container Terminals - Bowei Xu; Depei Jie; Junjun Li; Yunfeng Zhou; Hailing Wang; Huiyao Fan (Journal of Marine Science and Engineering, 2022)
Automated guided vehicles (AGVs) in the U-shaped automated container terminal travel longer and more complex paths. The conflicts among AGVs are trickier. The scheduling strategy of the traditional automated container terminal is difficult to be applied to the U-shaped automated container terminal. In order to minimize the handling time of all tasks and avoid AGV conflicts simultaneously in the U-shaped automated container terminal, this paper establishes a hybrid programming model for conflict-free integrated scheduling of quay cranes, AGVs, and double-cantilever rail cranes in the unloading process. It consists of a discrete event dynamic model and a continuous time dynamic model. An improved genetic seagull optimization algorithm (GSOA) is designed. A series of numerical experiments are conducted to verify the effectiveness and the efficiency of the model and the algorithm. The results show that the proposed method can simultaneously realize the AGVs collision avoidance and multi-equipment integrated scheduling optimization in the U-shaped automated container terminal.

Euler solution selecting method based on the damping factor - Liu Qiang; Yao Changli; Luo Yao; Yang Junjun; Li Zelin (Acta Geophysica, 2022)

Fine detection on water abundance of sandstone by joint inversion of seismic and CSAMT: a case study in the western Ordos Basin, China - Yi Dong; Jiulong Cheng; Laifu Wen; Peng Cheng; Fei Li; Junjun Jiao; Qisong Huang (Acta Geophysica, 2022)

Genetic and transcriptomic dissection of an artificially induced paired spikelets mutant of wheat (Triticum aestivum L.) - Juanyu Zhang; Yanyan Tang; Xi Pu; Xuebing Qiu; Jinhui Wang; Tao Li; Zhao Yang; Yao Zhou; Yuxiao Chang; Junjun Liang; Haili Zhang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2022)

Optimization of Container Shipping Network Reconfiguration under RCEP - Junjun Li; Hang Zhao; Bowei Xu (Journal of Marine Science and Engineering, 2022)
Due to its advantages of large transportation volume and low transportation cost, container shipping has become an important transportation mode in current international trade. The recovery of the shipping industry in 2021 and the signing of RCEP make the reconfiguration and optimization of the container shipping network a very important task at present. The network service capability is an important factor affecting the container shipping network. Based on the complex network theory, the coefficients of port location, the importance of distance and route among ports are taken as the service capacity reconfiguration coefficients of the global container shipping network. A max-min mixed integer model is established for global container shipping network reconfiguration. A sort of communication-reducing conjugate gradient method based on Krylov Subspace (CR-CG-KS) is proposed to reduce the reconfiguration computation. The results show that the global container shipping network does not need large-scale reconfiguration but requires small-scale changes to optimize the network feature vector centrality and make the network more balanced and stable. This study is beneficial for business managers to proactively respond to the future development of the shipping network and improve the operational efficiency of the global container shipping network.

Dynamic Appointment Rescheduling of Trucks under Uncertainty of Arrival Time - Bowei Xu; Xiaoyan Liu; Junjun Li; Yongsheng Yang; Junfeng Wu; Yi Shen; Ye Zhou (Journal of Marine Science and Engineering, 2022)
The uncertainty of the arrival time of trucks has increased the complexity of terminal operations. The truck appointment system (TAS) cannot respond to this problem in time, which can easily cause appointment invalidation and reduce the efficiency of truck operations and terminal operations. This paper comprehensively considers the related constraints of truck re-scheduling costs, gate waiting costs, and idle emission costs. With the goal of minimizing the comprehensive operating costs of truck companies and port companies, a dynamic appointment rescheduling model for external trucks based on mixed integer nonlinear programming is established. This paper designs an adaptive quantum revolving door update mechanism and proposes a double-chain real quantum genetic algorithm. The simulation experiment results show that compared with the traditional scheduling, the truck dynamic appointment rescheduling model can effectively reduce the comprehensive operating costs of the truck company and the port company and alleviate the congestion of the port. The probability that the truck cannot arrive at the port on time, the advance time for the truck to confirm the arrival time, and the length of time that the external truck cannot arrive at the port on time have a significant impact on the cost of the reschedule of the TAS. This paper favorably supports the manager’s operational decision-making.

A Flexible Scheduling for Twin Yard Cranes at Container Terminals Considering Dynamic Cut-Off Time - Junjun Li; Jingyu Yang; Bowei Xu; Wenjun Yin; Yongsheng Yang; Junfeng Wu; Ye Zhou; Yi Shen (Journal of Marine Science and Engineering, 2022)
Yard handling is an important part of port logistics and affects the overall efficiency of the container port. The yard crane scheduling is affected by various external factors. For example, the dynamic cut-off time makes the release time of yard cranes variable, and the yard crane task arrangement will change frequently, resulting in a lot of computational time. To increase the flexibility of container yard handling, a twin yard cranes scheduling model is established considering the no-crossing constraints and the dynamic cut-off time. A joint scheduling of PSO and local re-scheduling strategy (LRPSO) is put forward to deal with the problem faster and more effectively. Small-scale and large-scale experiments are simulated to verify the performance of the proposed method. Results show that the scheduling method is more efficient.

Correction to: Can “new infrastructure” reverse the “growth with pollution” profit growth pattern? An empirical analysis based on listed companies in China - Lu Qiao; Lin Li; Junjun Fei (Environmental Science and Pollution Research, 2022)

Can “new infrastructure” reverse the “growth with pollution” profit growth pattern? An empirical analysis based on listed companies in China - Lu Qiao; Lin Li; Junjun Fei (Environmental Science and Pollution Research, 2022)

The promotional effect of microRNA-103a-3p in cervical cancer cells by regulating the ubiquitin ligase FBXW7 function - Li Ren; Jinjin Yang; Xiyan Meng; Junjun Zhang; Yiran Zhang (Human Cell, 2022)
MicroRNAs (miRNAs) have been reported to be involved in the initiation and progression of human tumors including cervical cancer (CC). However, the mechanisms underlying of their actions in CC remain to be fully elucidated. Herein, the differentially expressed miRNAs that were screened based on GSE55940 microarray data retrieved from Gene Expression Omnibus (GEO), and miR-103a-3p was significantly upregulated in CC tissues which was selected as the target miRNA for further research. We also found that high expression of miR-103a-3p was closely associated with histological grades, FIGO stage and distant metastasis as well as reflected poor overall survival. Moreover, miR-103a-3p inhibition decreased the growth capacity of SiHa and HeLa cells by inducing cell apoptosis. And F-box and WD repeat-domain containing protein 7 (FBXW7), a well-known tumor suppressor in many cancer types, was identified as a direct target of miR-103a-3p. It was further found that FBXW7 was significantly downregulated in CC tissues, and it was inversely correlated with miR-103a-3p expression levels. Further investigation demonstrated that FBXW7 upregulation could simulate the roles of miR-103a-3p knockdown in cell viability and apoptosis. Moreover, FBXW7 knockdown efficiently abrogated the influences of CC cells proliferation caused by miR-103a-3p inhibition. Notably, miR-103a-3p could block FBXW7 mediated the downstream transcription factor pathways. Taken together, these findings suggest that miR-103a-3p functions as an oncogene in CC by targeting FBXW7.

How to promote sustainable adoption of residential distributed photovoltaic generation in China? An employment of incentive and punitive policies - Shuai Wang; Yao Li; Junjun Jia (Mitigation and Adaptation Strategies for Global Change, 2022)

Swimming behaviour of silver carp ( Hypophthalmichthys molitrix ) in response to turbulent flow induced by a D ‐cylinder - Senfan Ke; Zhiying Tu; Elsa Goerig; Junjun Tan; Bixin Cheng; Zhimin Li; Xiaotao Shi (Journal of Fish Biology, 2022)
Turbulence is a complex hydraulic phenomenon which commonly occurs in natural streams and fishways. Riverine fish are subjected to heterogeneous flow velocities and turbulence, which may affect their movements and ability to pass the fishways. However, studies focusing on fish response to turbulent flows are lacking for many species. Here we investigate the effects of the turbulence created by a vertical half‐cylinder of various diameters (1.9, 2.5, 3.2 and 5.0 cm) on the swimming ability and behaviour of silver carp, Hypophthalmichthys molitrix . The large D‐cylinders (3.0 and 5.0 cm) create specific vorticity and reduced velocities areas in their vicinity, which favours flow refuging behaviours (FRBs) and thus increased relative critical swimming speeds ( U rcrit , BL/s) of silver carp, by comparison to free‐flow conditions and cylinders of smaller diameter (1.9 and 2.5 cm). The flow speed at which silver carp maximized FRBs such as Karman gaiting downstream of the cylinder, holding position in the bow wake or entraining on the side ranged from 40 to 70 cm s −1 , depending on fish body size. When holding station near a cylinder under optimal flow speeds, the distance between the fish and the cylinder is related to the size of the fish, but also to the size of the cylinder and the produced vortices. The optimal holding region in the drag wake of the cylinder ranged from 28 to 40 cm downstream of the centre of the cylinder, depending on the size of the fish. Smaller fish, however, tend to use the reduced velocities areas located in the bow wake of the large cylinders. We hypothesize that fish will display FRBs, including maintaining a Karman gait in turbulent flow, when the ratio of the cylinder diameter to their body length is between 1:3 and 1:4. They also match their tail beat frequency to the vortex shedding frequency of the cylinder. Our results provide a better understanding of how silver carp respond to turbulent flows around physical structures, with implications for the design of nature‐like fishways or exclusion devices in both its native and invasive ranges.

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Joint Inversion and Application of DC and Full-Domain TEM with Particle Swarm Optimization - Yi Dong; Jiulong Cheng; Haijun Xie; Fei Li; Junjie Xue; Laifu Wen; Zhi Chen; Junjun Jiao (Pure and Applied Geophysics, 2022)

Differential Expression and Distinct Roles of Proteinase-Activated Receptor 2 in Microglia and Neurons in Neonatal Mouse Brain After Hypoxia-Ischemic Injury - Yicong Liu; Hui Li; Jiangqi Hu; Zhou Wu; Jie Meng; Yoshinori Hayashi; Hiroshi Nakanishi; Hong Qing; Junjun Ni (Molecular Neurobiology, 2022)

Geochemical characteristics and source of crude oil in the Shenhu uplift, Pearl River Mouth Basin, South China Sea - Xiaoyan Fu; Shijia Chen; Xin He; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Identification of the vertical sealing of faults by geochemical methods—taking the Zhu-3 sub-basin of the Pearl River Mouth Basin as an example - Xiaoyan Fu; Shijia Chen; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Effects of Acid Sulfate and Chloride Ion on the Pore Structure and Mechanical Properties of Sandstone Under Dynamic Loading - Xiaoliang Li; Zhentang Liu; Xiaojun Feng; Huajie Zhang; Junjun Feng (Rock Mechanics and Rock Engineering, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Substances for regenerative wound healing during antler renewal stimulated scar-less restoration of rat cutaneous wounds - Qianqian Guo; Zhen Liu; Junjun Zheng; Haiping Zhao; Chunyi Li (Cell and Tissue Research, 2021)

A Modified Self-adaptive Method for Mapping Annual 30-m Land Use/Land Cover Using Google Earth Engine: A Case Study of Yangtze River Delta - Le’an Qu; Manchun Li; Zhenjie Chen; Junjun Zhi (Chinese Geographical Science, 2021)

Hybrid Scheduling for Multi-Equipment at U-Shape Trafficked Automated Terminal Based on Chaos Particle Swarm Optimization - Junjun Li; Jingyu Yang; Bowei Xu; Yongsheng Yang; Furong Wen; Haitao Song (Journal of Marine Science and Engineering, 2021)
Aimed to improve the efficiency of port operations, Shanghai Zhenhua Heavy Industries Co., Ltd. (ZPMC) proposed a new U-shape trafficked automated terminal. The new U-shape trafficked automated terminal brings a new hybrid scheduling problem. A hybrid scheduling model for yard crane (YC), AGV and ET in the U-shape trafficked automated terminal yard is established to solve the problem. The AGV and ET yard lanes are assumed to be one-way lane. Take the YC, AGV and ET scheduling results (the container transportation sequences) as variables and the minimization of the maximum completion time as the objective function. A scheduling model architecture with hierarchical abstraction of scheduling objects is proposed to refine the problem. The total completion time is solved based on a static and dynamic mixed scheduling strategy. A chaotic particle swarm optimization algorithm with speed control (CCPSO) is proposed, which include a chaotic particle strategy, a particle iterative speed control strategy, and a particle mapping space for hybrid scheduling. The presented model and algorithm were applied to experiments with different numbers of containers and AGVs. The parameters of simulation part refer to Qinzhou Port. The simulation results show that CCPSO can obtain a near-optimal solution in a shorter time and find a better solution when the solution time is sufficient, comparing with the traditional particle swarm optimization algorithm, the adaptive particle swarm optimization algorithm and the random position particle swarm optimization algorithm.

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Temporal variability of free-living microbial culturability and community composition after an Akashiwo sanguinea bloom in Shenzhen, China - Huirong Chen; Junjun JIang; Fajun Jiang; Shuangfei Li; Zhangli Hu (Ecotoxicology, 2021)

MiR-874 Inhibits Cell Proliferation, Migration, and Invasion of Glioma Cells and Correlates with Prognosis of Glioma Patients - Yongjuan Li; Xiaoyan Chen; Wei Xue; Junjun Liang; Liang Wang (NeuroMolecular Medicine, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Bellamya aeruginosa (Reeve) regulates bacterial community features in sediment harbouring different submerged macrophytes under different nutrient levels - Junjun Chang; Bohua Ji; Wei Li; Jianping Wu (Aquatic Sciences, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Astragaloside protects rat brain from microwave-induced functional injuries via restoring acetylcholine and normalizing electroencephalogram - Li Zhao; Yunbo Sun; Chao Yu; Junjun Chen; Xinping Xu; Xueyan Zhang; Hui Wang; Jing Zhang; Haoyu Wang; Ji Dong; Binwei Yao; Hongmei Zhou; et al. (Environmental Science and Pollution Research, 2020)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Permeability-enhanced rate model for coal permeability evolution and its application under various triaxial stress conditions - Jing Xie; Mingzhong Gao; Junjun Liu; Cong Li; Gaoyou Peng (Arabian Journal of Geosciences, 2020)

The miR-15/16 Cluster Is Involved in the Regulation of Vertebrate LC-PUFA Biosynthesis by Targeting pparγ as Demonostrated in Rabbitfish Siganus canaliculatus - Junjun Sun; Cuiying Chen; Cuihong You; Yang Liu; Hongyu Ma; Óscar Monroig; Douglas R. Tocher; Shuqi Wang; Yuanyou Li (Marine Biotechnology, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Membrane proteomic analysis reveals the intestinal development is deteriorated by intrauterine growth restriction in piglets - Shimeng Huang; Cong Liu; Na Li; Zhenhua Wu; Tiantian Li; Dandan Han; Zhen Li; Jiangchao Zhao; Junjun Wang (Functional & Integrative Genomics, 2020)

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

Alleviation of the detrimental effect of water deficit on wheat (Triticum aestivum L.) growth by an indole acetic acid-producing endophytic fungus - Xiaojing Qiang; Junjun Ding; Wei Lin; Qiaozhen Li; Chunying Xu; Qian Zheng; Yuzhong Li (Plant and Soil, 2019)

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

The success of the representation maintenance affects the memory-guided search processing: an ERP study - Min Wang; Ping Yang; Zhenlan Jin; Junjun Zhang; Ling Li (Experimental Brain Research, 2019)

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Dual-functionality of RASSF1A overexpression in A375 cells is mediated by activation of IL-6/STAT3 regulatory loop - Mei Yi; Wei Wang; Shengnan Chen; Ya Peng; Junjun Li; Jing Cai; Ying Zhou; Qian Peng; Yuanyuan Ban; Zhaoyang Zeng; Xiaoling Li; Wei Xiong; et al. (Molecular Biology Reports, 2018)

Characterization of extracellular polysaccharide/protein contents during the adsorption of Cd(II) by Synechocystis sp. PCC6803 - Li Shen; Zhanfei Li; Junjun Wang; Ajuan Liu; Zhenhua Li; Runlan Yu; Xueling Wu; Yuandong Liu; Jiaokun Li; Weimin Zeng (Environmental Science and Pollution Research, 2018)

Vimentin is a crucial target for anti-metastasis therapy of nasopharyngeal carcinoma - Wei Wang; Mei Yi; Renya Zhang; Junjun Li; Shengnan Chen; Jing Cai; Zhaoyang Zeng; Xiaoling Li; Wei Xiong; Li Wang; Guiyuan Li; Bo Xiang (Molecular and Cellular Biochemistry, 2018)

Sustained-release study on Exenatide loaded into mesoporous silica nanoparticles: in vitro characterization and in vivo evaluation - Cuiwei Chen; Hongyue Zheng; Junjun Xu; Xiaowei Shi; Fanzhu Li; Xuanshen Wang (DARU Journal of Pharmaceutical Sciences, 2017)

Mapping soil organic carbon stocks of northeastern China using expert knowledge and GIS-based methods - Xiaodong Song; Feng Liu; Bing Ju; Junjun Zhi; Decheng Li; Yuguo Zhao; Ganlin Zhang (Chinese Geographical Science, 2017)

Nitric oxide-mediated cytosolic glucose-6-phosphate dehydrogenase is involved in aluminum toxicity of soybean under high aluminum concentration - Huahua Wang; Junjie Hou; Yan Li; Yangyang Zhang; Junjun Huang; Weihong Liang (Plant and Soil, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Histone acetylation and reactive oxygen species are involved in the preprophase arrest induced by sodium butyrate in maize roots - Qi Zhang; Pu Wang; Haoli Hou; Hao Zhang; Junjun Tan; Yan Huang; Yingnan Li; Jinping Wu; Zhengming Qiu; Lijia Li (Protoplasma, 2017)

Nitrate reductase-mediated nitric oxide production alleviates Al-induced inhibition of root elongation by regulating the ascorbate-glutathione cycle in soybean roots - Huahua Wang; Yan Li; Junjie Hou; Junjun Huang; Weihong Liang (Plant and Soil, 2017)

Involvement of nitric oxide-mediated alternative pathway in tolerance of wheat to drought stress by optimizing photosynthesis - Huahua Wang; Junjun Huang; Yan Li; Changan Li; Junjie Hou; Weihong Liang (Plant Cell Reports, 2016)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Paleogene lacustrine dolomitization, Xingou region, southern Qianjiang Depression, China - Junjun Shen; Bo Chen; Fangfang Chen; Chao Cheng; Yangfan Li; Ying Tian (Geosciences Journal, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)

Exogenous EDDS modifies copper-induced various toxic responses in rice - Junjun Tan; Shibin He; Shihan Yan; Yingnan Li; Hui Li; Hao Zhang; Lin Zhao; Lijia Li (Protoplasma, 2014)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

Heterologous expression and characterization of a malathion-hydrolyzing carboxylesterase from a thermophilic bacterium, Alicyclobacillus tengchongensis - Zhenrong Xie; Bo Xu; Junmei Ding; Lingyun Liu; Xuelin Zhang; Junjun Li; Zunxi Huang (Biotechnology Letters, 2013)

Determination of GABAAα1 and GABAB1 receptor subunits expression in tissues of gilts during the late gestation - Zhiyong Fan; Yonghui Chen; Junjun Wang; Jinping Deng; Dexing Hou; Tiejun Li; Lingyuan Yang; Zhonghua Liu; Xiaosong Wu (Molecular Biology Reports, 2013)

Zinc Inhibits H2O2-Induced MC3T3-E1 Cells Apoptosis via MAPK and PI3K/AKT Pathways - Dan Liang; Maowei Yang; Baolei Guo; Junjun Cao; Lei Yang; XiaoDong Guo; Yuanzhou Li; Zhida Gao (Biological Trace Element Research, 2012)

Expression of Nogo-66 receptor in human astrocytoma is correlated with tumor malignancy - Nanxiang Xiong; Jianying Shen; Shuai Li; Junjun Li; Hongyang Zhao (Molecular Biology Reports, 2012)

Tissue distribution and expression of signaling lymphocyte activation molecule receptor to peste des petits ruminant virus in goats detected by real-time PCR - Xuelian Meng; Yongxi Dou; Junjun Zhai; Hairui Zhang; Fengchao Yan; Xiaoni Shi; Xuelong Luo; Hui Li; Xuepeng Cai (Journal of Molecular Histology, 2011)

Assessing land ecological security in Shanghai (China) based on catastrophe theory - Shiliang Su; Dan Li; Xiang Yu; Zhonghao Zhang; Qi Zhang; Rui Xiao; Junjun Zhi; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2011)

Application of the equivalent offset migration method in acoustic log reflection imaging - Tiexuan Zhang; Guo Tao; Junjun Li; Bing Wang; Hua Wang (Applied Geophysics, 2009)

Plus- and minus-stranded foot-and-mouth disease virus RNA quantified simultaneously using a novel real-time RT-PCR - Chaojiang Gu; Congyi Zheng; Lili Shi; Qian Zhang; Yong Li; Bin Lu; Yi Xiong; Sanpu Qu; Junjun Shao; Huiyun Chang (Virus Genes, 2007)

Design and Structure--Activity Relationship of Novel Endothelin Receptor A Tripeptide Antagonists - Junjun Dong; Ning Yang; Yuanjun Liang; Ping Wu; Xin Li; Keliang Liu (International Journal of Peptide Research and Therapeutics, 2005)